INTEGRATED WEB MOBILE INFORMATION SYSTEM FOR OPTIMIZING ADMINISTRATIVE MANAGEMENT OF ROUDATUL JANNAH ISLAMIC BOARDING SCHOOL - Marlia Sari; Lusia Septia Eka Esti Rahayu; Muhammad Rasid; Muhammad Junaid (Penerbit Goodwood, 2026)
Purpose: This study analyzes the optimization of Islamic boarding school administrative management through an integrated information system to improve service effectiveness, data accuracy, and administrative efficiency.Research Methodology: This study applies the System Development Life Cycle (SDLC), including planning, requirements analysis, design, implementation, testing, and maintenance. Data were collected through observations, interviews, and documentation.Results: The integrated web-mobile information system successfully met all functional requirements based on Black Box Testing and received positive user evaluations for usability and accessibility. The system improved data processing, information accuracy, reporting, transparency, and administrative services while supporting better monitoring and decision-making.Conclusion: The implementation of the integrated web-mobile information system effectively enhanced the efficiency and quality of administrative management at the Roudatul Jannah Islamic Boarding School, demonstrating its potential as a practical digital solution for Islamic boarding school administration.Limitations: The study was conducted in a single Islamic boarding school, limiting the generalizability of the findings.Contribution: This study proposes an integrated administrative information system model that supports the digital transformation and effectiveness of Islamic boarding school administration.